2014
DOI: 10.1007/s40272-014-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethics of Drug Research in the Pediatric Intensive Care Unit

Abstract: Critical illness and treatment modalities change pharmacokinetics and pharmacodynamics of medications used in critically ill children, in addition to age-related changes in drug disposition and effect. Hence, to ensure effective and safe drug therapy, research in this population is urgently needed. However, conducting research in the vulnerable population of the pediatric intensive care unit (PICU) presents with ethical challenges. This article addresses the main ethical issues specific to drug research in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 84 publications
0
17
0
1
Order By: Relevance
“…The influence of critical illness, such as renal or liver failure, release of vasoactive cytokines, as well as specific therapies such as extracorporeal membrane oxygenation will influence dosing regimens [35]. For example, in neonates undergoing total body cooling there is animal evidence that dobutamine will accumulate, presumably due to a reduction in the activity of catechol-O-methyl transferase [70].…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of critical illness, such as renal or liver failure, release of vasoactive cytokines, as well as specific therapies such as extracorporeal membrane oxygenation will influence dosing regimens [35]. For example, in neonates undergoing total body cooling there is animal evidence that dobutamine will accumulate, presumably due to a reduction in the activity of catechol-O-methyl transferase [70].…”
Section: Future Researchmentioning
confidence: 99%
“…Both the European Medicines Agency in their priority list for studies into off-patent pediatric medicinal products and the US National Institutes of Health in their Best Pharmaceuticals for Children Act have highlighted dobutamine as a drug that requires further investigation [18,35].…”
Section: Introductionmentioning
confidence: 99%
“…Podaci o primjeni lijekova ekstrapoliraju se iz podataka za odraslu populaciju, zbog čega doziranje predstavlja glavni izazov u terapijama pedijatrijske populacije [3][4] . No, svaki lijek korišten u praksi, koji nije ispitan u kliničkim ispitivanjima, može se smatrati eksperimentom 5 . Zakonodavni čimbenici, manjak gospodarskog interesa farmaceutske industrije, odraz negativnih rezultata na upotrebu lijeka u odrasloj populaciji te odgođene neželjene reakcije na lijekove uzrok su nedostataka podataka o primjeni lijekova u pedijatrijskoj populaciji, što tu populaciju dovodi do statusa 'terapijske siročadi' [6][7][8] .…”
Section: Uvodunclassified
“…There are challenges associated with performing pharmacokinetic studies in neonatal and some pediatric patients due to their small blood volumes and the psychological burden associated with blood sampling. 25 Studies have found that pediatric intensivists are in ethical conflict about performing potentially life-saving drug research, even while identifying them as ethically acceptable. 25 Yet, this information is important for optimizing the treatment of their patients.…”
Section: Introductionmentioning
confidence: 99%